The Influence of Religious Intellectual Humility (IH) in the Learning Process Shapes Student Tolerance Behavior - Pelupessy, Muhammad Kashai Ramdhani; Abidin, Andi Rahmat; Pattimahu, M. Asrul (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose –Understanding of religious extremism has begun to enter the world of campuses in Indonesia today. Of course, this has an impact on intolerance behavior. Recent studies show that religious intellectual humility (IH) can shape a person's tolerant behavior. But so far, this topic has been minimally replicated in the learning process in Indonesia. Therefore, this research seeks to prove and explain the influence of religious IH in the learning process in shaping students' tolerant behavior. Design/methods/approach–This study is an ex-post facto research. The subjects were lecturers (29 people) and students (41 people) at Islamic Education Department (IED) from one of the Islamic universities in Maluku. Data collection techniques use the IHS scale, RHS, and tolerance behavior scale. Data analysis used a simple linear regression technique. Findings –The results of the study show that there is an influence of religious IH in the learning process to shape student tolerance behavior by p = 0,000 (p<0,05). The contribution of religious IH forms tolerance behavior of 76.2%. This means that apart from religious IH, around 23.8% of other variables also shape tolerant behavior such as empathy, self-disclosure, and giving support for the rights of others. Research implications/limitations –The limitation of this research is that the subject comes from a limited number of lecturers and students in Maluku. In addition, this study also did not use an experimental design. It is suggested that the next study needs to involve a large number of samples (educators and students), it is also expected that it needs to be replicated in the form of an experimental design. Originality/value –This study recommends educators (lecturers) continue to practice religious IH in the learning process, especially for their students (prospective IED teachers) so that later they can practice it in the IED learning process in the future.